Menabung dan Berbagi: Menanamkan Nilai-Nilai Positif dan Mencegah Penyalahgunaan Narkoba pada Anak-Anak TPA Al-Ma’ruf - Nainggolan, Yohanna Thresia; Sari, Mayang; Zulfaini, Umi Devina; Krisna, Krisna; Mailin, Mailin; Mildawati, Asrianti (LPMP Imperium, 2025)
Selumit Pantai Sub-district in Tarakan City, North Kalimantan, is known as a “Drug Village” due to the widespread circulation and trade of narcotics. This community service initiative aimed to instill positive values and improve financial literacy among children at TPA Al-Ma’ruf as a preventive measure against drug abuse. A practical approach fostered emotional engagement between participants and educators, making learning more accessible and enjoyable. The activity was conducted face-to-face on April 29, 2025, at Al-Ma’ruf Mosque and involved 41 children aged 5–14. Evaluation results indicated an improved understanding of basic money management, along with high enthusiasm and active participation. The provision of savings rewards was a positive stimulus to cultivate saving and sharing habits. This program demonstrates that affective-based education combined with financial literacy can effectively shape positive behavior and prevent early exposure to drugs.